Destabilizing the genome as a therapeutic strategy to enhance response to immune checkpoint blockade: a systematic review of clinical trials evidence from solid and hematological tumors - Alotaibi, Faizah; Alshammari, Kanaan; Alotaibi, Badi A.; Alsaab, Hashem (Frontiers in Pharmacology, 2024)
Background: Genomic instability is increased alterations in the genome during cell division and is common among most cancer cells. Genome instability enhances the risk of initial carcinogenic transformation, generating new clones of tumor cells, and increases tumor heterogeneity.Although genome instability contributes to malignancy, it is also an "Achilles' heel" that constitutes a therapeutically-exploitable weaknesswhen sufficiently advanced, it can intrinsically reduce tumor cell survival by creating DNA damage and mutation events that overwhelm the capacity of cancer cells to repair those lesions. Furthermore, it can contribute to extrinsic survival-reducing events by generating mutations that encode new immunogenic antigens capable of being recognized by the immune system, particularly when anti-tumor immunity is boosted by immunotherapy drugs. Here, we describe how genome-destabilization can induce immune activation in cancer patients and systematically review the induction of genome instability exploited clinically, in combination with immune checkpoint blockade.We performed a systematically review of clinical trials that exploited the combination approach to successfully treat cancers patients. We systematically searched PubMed, Cochrane Central Register of Controlled Trials, Clinicaltrials.gov, and publication from the reference list of related articles. The most relevant inclusion criteria were peer-reviewed clinical trials published in English.We identified 1490 studies, among those 164 were clinical trials. A total of 37 clinical trials satisfied the inclusion criteria and were included in the study. The main outcome measurements were overall survival and progression-free survival. The majority of the clinical trials (30 out of 37) showed a significant improvement in patient outcome.The majority of the included clinical trials reported the efficacy of the concept of targeting DNA repair pathway, in combination with immune checkpoint inhibitors, to create a "ring of synergy" to treat cancer with rational combinations.